Low-pressure versus standard pressure laparoscopic colorectal surgery (PAROS trial): a phase III randomized controlled trial. Issue 8 (23rd March 2021) - Celarier, S; Monziols, S; Célérier, B; Assenat, V; Carles, P; Napolitano, G; Laclau-Lacrouts, M; Rullier, E; Ouattara, A; Denost, Q
Abstract: Trial design: This is a phase III, double-blind, randomized, controlled trial. Methods: In this trial, patients with laparoscopic colectomy were assigned to either low pressure (LP: 7 mmHg) or standard pressure (SP: 12 mmHg) at a ratio of 1 : 1. The aim of this trial was to assess the impact of low-pressure pneumoperitoneum during laparoscopic colectomy on postoperative recovery. The primary endpoint was the duration of hospital stay. The main secondary endpoints were postoperative pain, consumption of analgesics and postoperative morbidity. Results: Some 138 patients were enrolled, of whom 11 were excluded and 127 were analysed: 62 with LP and 65 with SP. Duration of hospital stay (3 versus 4 days; P  = 0.010), visual analog scale (0.5 versus 2.0; P  = 0.008) and analgesic consumption (level II: 73 versus 88 per cent; P  = 0.032; level III: 10 versus 23 per cent; P  = 0.042) were lower with LP. Morbidity was not significantly different between the two groups (10 versus 17 per cent; P  = 0.231). Conclusion: Using low-pressure pneumoperitoneum in laparoscopic colonic resection improves postoperative recovery, shortening the duration of hospitalization and decreasing postoperative pain and analgesic consumption. This suggests that low pressure should become the standard of care for laparoscopic colectomy. Trial registration: NCT03813797 Lay summary: The aim of this trial was to assess the impact of low-pressure pneumoperitoneum during laparoscopic colectomy. The study proved that using low pressure in laparoscopic colonic resection improves postoperative recovery, decreasing length of hospitalization, postoperative pain and analgesic consumption. Abstract : The aim of this trial was to assess the impact of low-pressure pneumoperitoneum during laparoscopic colectomy. We proved that using low pressure in laparoscopic colonic resection improves post-operative recovery, decreasing both length of hospitalization, post-operative pain and analgesic consumption.